PENGARUH VOLATILITAS HARGA SAHAM, FREKUENSI PERDAGANGAN DAN RETURN SAHAM TERHADAP BID-ASK SPREAD PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 PERIODE 2019 – 2022 - Husni, Mohamad; Anggriawan, Muhammad Angga; Wahyuni, Nur (Universitas Nusa Cendana, 2024)
The objective of this study is to determine the impact of variable volatility of stock price, trading frequency, and share returns on bid-ask spreads either partially or simultaneously for LQ45 index member companies. The quantitative method is the method used in the study, the population in this study was 45 companies listed in the LK45 index, whereas, for the sample this study used 8 companies with the observation period 2019-2022, the findings in this research had a negative and significant effect on the price-ask variable bid spread, while for Frequency Trading and Share Return Variables did not affect the bid-ash spread it was marked by the reevaluation value of trading currency and stock return variability, while to test jointly on the entire variable value of the price of stocks, frequencies, and trade per share significantly affected the return of stocks in terms of the value of bid-assets being divided. This study concludes that by understanding the impact of stock price volatility and trading frequency, investors can develop better strategies to manage risk and maximize profits. Keywords: Stock Price Volatility; Trading Frequency; Stock Return; Bid-ask spread